(947) Economic and Financial Developments in the Economy of U.A.R التطورات الاقتصادية والمالية في اقتصاد الجمهورية العربية المتحدة - Hassan M. Selim. (The Institute of National Planning, 2025)
In this paper, we will address the relationship between economic and financial developments in the United Arab Republic during the period from 1952 to 1966. The aim is to explore the sources of capital accumulation in the development process and the planning period from 59/60 to 64/65, along with the expansionary financial pressure that followed, which contributed to the growing deficit in the balance of payments. Excess demand, which manifested itself in the balance of payments deficit, will also be discussed within the framework of economic analysis. The data reveals the economic growth of the UAR during the period 1952-1966.